The Holocene Labrador Current: Changing linkages to atmospheric and oceanographic forcing factors. (23rd May 2017) - Rashid, Harunur; Piper, David J. W.; Lazar, Kelly B.; McDonald, Kieran; Saint‐Ange, Francky
Abstract: The role of Labrador Current (LC) in providing freshwater to the North Atlantic and hence modulating the Atlantic meridional overturning circulation (AMOC) has been debated with very few data. This study provides the first data on the relative speed of the LC for the past 9.2 ka using mean size of the sortable silt of sediments as a proxy from a midshelf basin in the western Labrador Sea. LC speed progressively intensified from 9.2 to 5 ka, during which two meltwater events had minor influence. The LC was fastest between 5 ka and 3.1 ka and gradually weakened after 3.1 ka. The mean size of the sortable silt data shows overall covariations with similar existing data from deepwater areas of the greater North Atlantic, suggesting an overarching link that modulates changes in both the near‐surface and deep North Atlantic. A dynamical link between the LC and AMOC vigor is hypothesized in which high meltwater discharge in the Labrador Sea oriented the subpolar gyre (SPG) more north‐south (meridional), weakening the SPG and thus decelerating the upper limb of the AMOC. Conversely, reduction in LC transport during the late Holocene, due to the greater export of sea ice, oriented the SPG more east‐west. Key Points: First reconstruction of the Labrador Current vigor using sediment dynamic mean size of the sortable silt proxy Early Holocene Labrador Current vigor shows continual intensification Late Holocene solar insolation modulates the vigor of the Labrador Current